Ciri-Ciri Spesifikasi Aplikasi untuk Pembangunan Kawalan Proses Statistik - Ahmad, Md. Fauzi; Ali, Mohammad Kamarulzzaman; Ahmad, Ahmad Nur Aizat (Research in Management of Technology and Business, 2021)
Statistical Process Control (SPC) is a quality control (QC) tool that use statistical methods to monitor a process in production line. This helps ensure that the process runs efficiently, producing products that comply with specifications. The main components used in SPC are control charts such as X and R chart, X and S chart, n chart, np chart, u chart, c chart. However, operators with limited knowledge of SPC face difficulties in using commercial software that requires high technical skill. In this study, basic visual applications were developed specifically to assist in the implementation of SPC. The methodology used in this study is an interview with ABC company employees to identify the specification features on KPS software that must be present in the Visual Basic Application to produce SPC software that is competitive with SPC software products. From this study, features of application specifications for statistical process control development have been developed for SPC software development.